Histoenzymological studies on stomach of crossbred bull calf - Choudhuri, K B Dey; Borthakur, S; Sarma, K; Sarma, M (The Indian Journal of Animal Sciences, 2011)
Study was conducted on the stomach of 9 crossbred bullcalf (HP x Local) of Assam age between 45-95 days. The histoenzymic activity of LDR, MDH and G-6-PD showed varying degree of intensity in all strata of forestomach except stratum corneum. The surface and glandular epithelium of abomasums contained LDH, MDH and G-6PD granules. AKPase and ACPase showed weak to intense activity in all strata of fore-stomach. AKPase was absent or showed weak to moderate activity whereas ACPase showed weak to strong activity in surface and grandular epithelium.